RZYMSKA GENEZA INSTYTUCJI ZAWIADOMIENIA DŁUŻNIKA O PRZELEWIE WIERZYTELNOŚCI. DENUNTIATIO Z C. 8,41,3 PR. A WYBRANE USTAWODAWSTWA WSPÓŁCZESNE - Ściślicki, Piotr (Zeszyty Prawnicze, 2017)
THE ROMAN ORIGINS OF THE NOTICE TO DEBTOR OF ASSIGNMENT DENUNTIATIO IN C. 8,41,3 PR. AND SELECTED CONTEMPORARY LEGAL SYSTEMS Summary The transferability of relative rights is now commonly admitted as one of the most basic and indispensable foundations of economic turnover. The creditor’s right, to which there corresponds a duty o f some designated individual, is considered to be first and foremost a fraction of capital, an element o f property broadly construed, capable of being alienated. The subjective level of a right, the fact that it belongs to one concrete person against an other, does not constitute its crucial and defining aspect. The standpoint of classical Roman law was, at least initially, different - iurisprudentes used to consider obligatio as a strictly personal legal bond which could not be affected by any subjective transformations. As such a rule did not correspond to commercial needs, there appeared a strong tendency to overcome it by means of legal instruments which to some extent did the work of assignment - novation with a change of subject, based on the Roman delegatio and the appointment of an attorney, authorized by the creditor to sue for the debt in the creditor’s name without any liability to account him (procuratio in rem suarri). Both devices, forms of Roman, so to say, quasi-cessioy were nothing but palliatives of assignment and as such had many disadvantages. Novation as a contract where the debt owed by the debtor would henceforth be owed to a third party does not preserve the identity o f the legal relation - the third party’s quasi-assignee’s) right against the obligor is based on the new contract between him and the debtor, while the original debt and correlative creditor’s (quasi- -assignor’s) right cease to exist. The power of attorney however can be revoked at any time by the creditor. Moreover, the quasi-assignor is here still able to sue the debtor personally and thus to deprive the quasi-assignee o f the acquired right. It is disputable whether Roman law ultimately worked out the idea of assignment. Some Romanists claim it never happened. However, according to the alternative view, the methods elaborated by classical jurisprudence to evade unpractical restriction, especially procuratio in rem suam, were gradually improved and endowed with properties that finally converted them into a form notionally equivalent to the contemporary understanding o f assignment. As has already been stated, in the light o f contemporary legal systems creditor’s rights against the debtor can be freely transferred to a third party by a process called assignment without affecting the identity o f the legal bond. The debtor is not a party to the transaction and his consent is not necessary to its validity. After a valid assignment is made, the assignee substitutes for the assignor as the person to whom performance must be rendered. There appears a risk that the debtor, unaware of the change, could still treat the assignor to be an obligee and consequently render the performance to him. Such an undue performance in principle does not discharge the obligation and thus the debtor’s responsibility to the assignee remains. It therefore follows that although the obligor need not be a party to or assent to the assignment, he should be notified of it so that he knows the person to whom performance is now due. The notification to the debtor (denuntiatio) has its origins in Codex Iustinianus - C. 8,41,3 pr. The point of this paper is to outline the influence of the above mentioned source upon some selected contemporary civil law systems, sc. French, Italian, Austrian, German, Swiss and Polish. The Roman concept of denuntiatio appears in all of them as the crucial element of the legal construction o f assignment. Furthermore, it seems to be the case that different ways of interpreting C. 8,41,3 postulated by the romanists have been reflected in the manifold of models according to which the contemporary cession is formed by lawmakers of different countries. It has to be underlined that the variety of possible schemes of assignment depends to a large extent on what legal significance is being attached to the denunciation - on whether it is considered to be the condition of validity or efficacy o f the transaction between assignor and assignee or whether it serves only as a contrivance to deprive the debtor of the possibility of rendering the performance in favor o f the assignor with the effect of discharging the obligation. The modifications of the Roman norm in the aforesaid legislations fall into three categories: 1) the legal significance of denuntiatio - what is the impact o f notification on the legal relation between assignor and assignee, 2) the technical aspect of notification - what is self-contained denunciation, who is enabled to perform it, what formalities are required for the notice, 3) the equivalents of denunciation - are there any states of affairs that bring about identical effects as self-contained notification, what is the status of the obligor’s pure, informal knowledge about the assignment from this point of view. Some remarks concerning common law systems aim at emphasizing the considerable similarities between them and continental legislations concerning the way in which they regulate the transfer of rights. Here notification plays an analogical role - it has a similar nature, relevance and consequences.